Nanoscale interfacial engineering enables highly stable and efficient perovskite photovoltaics. Issue 10 (16th September 2021) - Krishna, Anurag; Zhang, Hong; Zhou, Zhiwen; Gallet, Thibaut; Dankl, Mathias; Ouellette, Olivier; Eickemeyer, Felix T.; Fu, Fan; Sanchez, Sandy; Mensi, Mounir; Zakeeruddin, Shaik M.; Rothlisberger, Ursula; et al.
Abstract : The molecular level interface engineering with a multifunctional ligand 2, 5-thiophenedicarboxylic acid suppresses interfacial ion diffusion and inhibits I2 formation, which leads to high operational stability with T 80 of 3570 h along with PCE of 23.4%. Abstract : We present a facile molecular-level interface engineering strategy to augment the long-term operational and thermal stability of perovskite solar cells (PSCs) by tailoring the interface between the perovskite and hole transporting layer (HTL) with a multifunctional ligand 2, 5-thiophenedicarboxylic acid. The solar cells exhibited high operational stability (maximum powering point tracking at one sun illumination) with a stabilized T S80 (the time over which the device efficiency reduces to 80% after initial burn-in) of ≈5950 h at 40 °C and a stabilized power conversion efficiency (PCE) over 23%. The origin of high device stability and performance is correlated to the nano/sub-nanoscale molecular level interactions between ligand and perovskite layer, which is further corroborated by comprehensive multiscale characterization. These results provide insights into the modulation of the grain boundaries, local density of states, surface bandgap, and interfacial recombination. Chemical analysis of aged devices showed that molecular passivation suppresses interfacial ion diffusion and inhibits the photoinduced I2 release that irreversibly degrades the perovskite. The interfacial engineering strategies enabled by multifunctional ligands can expedite the path towards stable PSCs.